2009
DOI: 10.1039/b9pp00086k
|View full text |Cite
|
Sign up to set email alerts
|

Drug efflux transporters, MRP1 and BCRP, affect the outcome of hypericin-mediated photodynamic therapy in HT-29 adenocarcinoma cells

Abstract: Photodynamic therapy (PDT) is a flexible multi-target therapeutic approach. One of the main requirements of successful PDT is sufficient intracellular concentration of an applicable photosensitizer. Mechanisms of anticancer drug elimination by tumour cells are mostly linked to the elevated expression and activity of P-glycoprotein (P-gp), multidrug resistance-associated protein 1 (MRP1), breast cancer resistance protein (BCRP) and P450 monooxygenases. The interaction of hypericin with this cell drug-defence sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 32 publications
3
42
0
Order By: Relevance
“…The specific inhibition of COX, LOX and CYP450 activity increased the efficacy of HY-PDT in the HT-29 cancer cell line (121). An important role for the MRP1 and BCRP transporters in HY efflux was also demonstrated (119). Proadifen, a P450 monooxygenase inhibitor, was shown to inhibit these transport proteins, resulting in a significant increase in intracellular HY accumulation in HT-29 cells and MRP1 and BCRP-overexpressing cells.…”
Section: Combination Of Nsaids With Chemotherapeutic Drugs In Vitromentioning
confidence: 93%
See 1 more Smart Citation
“…The specific inhibition of COX, LOX and CYP450 activity increased the efficacy of HY-PDT in the HT-29 cancer cell line (121). An important role for the MRP1 and BCRP transporters in HY efflux was also demonstrated (119). Proadifen, a P450 monooxygenase inhibitor, was shown to inhibit these transport proteins, resulting in a significant increase in intracellular HY accumulation in HT-29 cells and MRP1 and BCRP-overexpressing cells.…”
Section: Combination Of Nsaids With Chemotherapeutic Drugs In Vitromentioning
confidence: 93%
“…COX-2 was found to be involved in the regulation of P-gp, MRP1 and BCRP transporter expression via the COX-2/PGE2̸PGE receptor 4̸phosphatidyl inositol 3-kinase pathway (116,118). Synergistic effects of NSAIDs with hypericin (HY)-mediated photodynamic therapy (PDT) have also been reported (119)(120)(121)(122). The specific inhibition of COX, LOX and CYP450 activity increased the efficacy of HY-PDT in the HT-29 cancer cell line (121).…”
Section: Combination Of Nsaids With Chemotherapeutic Drugs In Vitromentioning
confidence: 99%
“…39 Jendzelovský et al showed that Proadifen, an inhibitor of cytochrome P450 enzymes, could a®ect the function of BCRP and MRP1 leading to increased hypericin content in colon cancer cells (HT-29 cells). 40 BCRP-mediated PpIX e®lux was also a major factor that prevented PpIX accumulation in human urothelial carcinoma cells (T24 cells). 41 Bebes et al showed that the PpIX extrusion ability of keratinocytes (HaCaT cells) was correlated with their BCRP expression which was higher in proliferating cells than in di®erentiated cells.…”
Section: Bcrp and Ps Uptakementioning
confidence: 99%
“…In order to measure the intensity of HYP fluorescence in the cells CellQuestPro software was used. HYP content was evaluated as mean fluorescence intensity (MFI) and as the ratio of MFI in treatment/control group (relative fluorescence intensity, RFI) (Jendzelovsky et al 2009). …”
Section: Analysis Of Hypericin Contentmentioning
confidence: 99%